Valor de la escala ORBIT en la predicción de eventos hemorrágicos en pacientes con fibrilación auricular en anticoagulación del Hospital Belén de Trujillo - Arroyo Cossio, Humberto (2022)
Atrial fibrillation is one of the most frequent cardiac arrhythmias and systemic thrombotic phenomena is one of its main complications, which is why oral anticoagulation is a frequent prescription in a large percentage of these patients, with the appearance of bleeding an adverse reaction from the use of this pharmacological group; It is a priority to design bleeding event prediction systems in order to improve quality of life and fine-tune control and follow-up strategies to guarantee the effectiveness but increase the safety of this therapeutic strategy. Objective: To demonstrate if the ORBIT scale has value in the prediction of hemorrhagic events in patients with atrial fibrillation receiving anticoagulation at Hospital Belén de Trujillo. Methodology: The study will be sectional, cross-sectional, retrospective of diagnostic tests. Population: 176 Patients older than 15 years, of both sexes; on anticoagulation therapy with warfarin; in whose medical records data corresponding to the mortality of patients under study with atrial fibrillation treated in the Department of Internal Medicine of the Hospital Belén de Trujillo during the period 2016-2020 is recorded